From core belief challenge to posttraumatic growth in para sport athletes: moderated mediation by needs satisfaction and deliberate rumination. Issue 20 (25th September 2019) - Hammer, Chris; Podlog, Leslie; Wadey, Ross; Galli, Nick; Forber-Pratt, Anjali J.; Newton, Maria
Abstract: Purpose: To examine how deliberate rumination and psychological need satisfaction interact to facilitate posttraumatic growth for para sport athletes with acquired disability. Methods: Utilizing a sample of 70 para sport athletes, the hypothesized mediating role of deliberate rumination was examined via a simple mediation model. The interaction between needs satisfaction and deliberate rumination and their effect on posttraumatic growth was examined utilizing a moderated mediation procedure. Results: Disruption to one's core beliefs was significantly associated with posttraumatic growth. This relationship, was in part, explained by the deliberate rumination engaged in soon after the trauma. Needs satisfaction, while a significant predictor of posttraumatic growth, did not moderate the indirect effect. Conclusions: Although deliberate rumination at both timeframes and needs satisfaction were independently associated with posttraumatic growth, they did not interact in the hypothesized manner to influence posttraumatic growth. There remains a need to better understand how the experience of posttraumatic growth is achieved amongst individuals with acquired disability, and the role that para sport may play in this process. Implications for rehabilitation: The disruption to one's core beliefs caused by acquiring a physical disability is not only a natural experience but also a necessary antecedent to posttraumatic growth. As such, rehabilitation practitioners ought to normalize these types of challenges when working with individuals with acquired disability. Practitioners may help to facilitate growth outcomes by encouraging individuals to deliberately ruminate about their acquired disability. That is, practitioners can help those with acquired disability to seek meaning and understanding about their disability or the precipitating event. For those who struggle to deliberately ruminate in the immediate disability aftermath, practitioners may encourage para sport participation to potentially prompt constructive cognitive processing. Individuals with acquired disabilities would also be well served by rehabilitation practitioners and para sport organizations that provide opportunities for basic psychological needs satisfaction. Specifically, individuals with acquired disabilities should be given the opportunity to demonstrate physical competence, make meaningful relationships, and feel a sense of volitional control over their rehabilitation or para sport participation. For example, practitioners and para sport organizations could establish mentorship programs wherein individuals with more recent disabilities can be mentored by those with greater disability experience.